PERAN SOSIAL MEDIA DALAM PERUBAHAN GAYA HIDUP KONSUMTIF REMAJA PEREMPUAN - Fitri Anggreni Kusuma (Universitas Katolik Widya Karya Malang, 2021)
In the modern era, internet users and social mediaincreased substantially. All the information can be easilysearched. Thus, teenage girls can be easily influenced by thelifestyle of contemporary trends while accessing social media. Itis used by many people to sell online. Teenage girls can easilybuy goods or just supporting current lifestyle. The purpose ofthis article is to determine the role of social media in thechanging consumer lifestyle adolescent girls. This article iswritten from the six previous journal within the last 10 years.With the ease of accessing the internet and the ease of socialmedia , young women can easily view the latest trend ofIndonesian artists and foreign artists dann it meimbulkanteenage girls want to keep abreast of current lifestyle . Thisshows that the role of social media in the changing consumerlifestyle teenage girls. Adolescent girls should be taught to usesocial media wisely and to avoid behavior directed konumtif